2010
DOI: 10.1016/j.neuroimage.2009.10.064
|View full text |Cite
|
Sign up to set email alerts
|

Cortical substrate of bladder control in SCI and the effect of peripheral pudendal stimulation

Abstract: We investigated (i) the central representation of lower urinary tract (LUT) control and (ii-iii) the acute and short-term central neuromodulatory effect of peripheral pudendal nerve stimulation in incomplete spinal cord injured (SCI) patients using functional magnetic resonance imaging (fMRI). The urinary bladder of eight SCI patients has been passively filled and emptied using a catheter, to identify the neural substrate of bladder control (i), and with simultaneous peripheral pudendal nerve stimulation to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 35 publications
1
17
0
5
Order By: Relevance
“…In animal lesion as well as neuroimaging studies, forebrain structures including the PFC and the ACC were found to play a modulatory role in the firing of the voiding reflex (Andrew and Nathan, ; Athwal et al, ; Blok et al, ; Kuhtz‐Buschbeck et al, ; Maurice‐Williams, ; Michels et al, in press). Similar observations have been reported in patients with spinal cord lesions (Zempleni et al, ), PFC underperfusion (Griffiths et al, ), and stroke (Sakakibara et al, ). In fact, the significance of the PFC in the continence and healthy UB function was initially established in clinical studies by Ueki (), and Andrew and Nathan ().…”
Section: Discussionsupporting
confidence: 83%
“…In animal lesion as well as neuroimaging studies, forebrain structures including the PFC and the ACC were found to play a modulatory role in the firing of the voiding reflex (Andrew and Nathan, ; Athwal et al, ; Blok et al, ; Kuhtz‐Buschbeck et al, ; Maurice‐Williams, ; Michels et al, in press). Similar observations have been reported in patients with spinal cord lesions (Zempleni et al, ), PFC underperfusion (Griffiths et al, ), and stroke (Sakakibara et al, ). In fact, the significance of the PFC in the continence and healthy UB function was initially established in clinical studies by Ueki (), and Andrew and Nathan ().…”
Section: Discussionsupporting
confidence: 83%
“…After 2 weeks of pudendal stimulation treatment, PAG activation to bladder filling was decreased. The authors suggest that the PAG may be overactive in spinal cord injured patients due to a de compensatory mechanism following the sudden loss of the spinal afferent input (Zempleni et al, 2010). …”
Section: Resultsmentioning
confidence: 99%
“…[7] Previous studies have shown that urge during bladder distension has been associated with activation of the periaqueductal gray (PAG), anterior cingulate gyrus, insula, thalamus, and cerebellum. [12951]…”
Section: Introductionmentioning
confidence: 99%